Immunohistochemical expression of ATRX in gliomas - Jalal, Jalal Ali; Rowandizy, Anjam Ibrahim Sulaiman; Ismael, Ava Taher (Cellular and Molecular Biology, 2020)
Glioma is one of the primary tumors of the central nervous system that occurs in the spinal cord or brain and the origin of the tumor is from glial cell cells. The most common site of glioma tumors is the brain. Glioma accounts for 30% of all central nervous system tumors and 80% of malignant brain tumors. Alpha-thalassemia/mental retardation syndrome X-linked (ATRX) mutations are frequently distinguished in gliomas. Current research is an attempt to assess ATRX immunoexpression in different types of gliomas diagnosed, in Erbil-Iraq, and to evaluate its association with patient’s age, gender, tumor location, grade and type. From January 2015 to January 2017, we reviewed and analyzed 97 cases of glioma. Immunohistochemical staining, for ATRX, was performed using an automated immunostainer technique. According to the WHO grading system for brain tumors, 16 (16.5%) cases were grade I gliomas, 27 (27.8%) were grade II, 10 (10.3%) were anaplastic gliomas (grade III), and 44 (45.3%) cases were glioblastomas WHO (grade IV). Positive ATRX immunoexpression was demonstrated in 27 (27.8%) cases. The highest rates of ATRX expression (55.6%) were among 30-39 years’ age group, supratentorial (34.2%), and among grade II and III tumors (40.7% and 30% respectively). A significant association was observed between ATRX expression and patient’s age, tumor location, tumor type and grade (p-values 0.010, 0.004, 0.004, and 0.037 respectively). No significant association was found between ATRX expression and patient’s gender (p-value 0.097). It was found that ATRX is frequently expressed in grade II and III astrocytomas and was significantly related to the patient’s age, tumor location, type and grade, so it can be used as a good diagnostic and prognostic indicator for glioma.